Serviço Técnico de Informática - Contel, André José; Batagelo, André Luís; Silva, Antonio Benedito da; Maeoka, Katia Midori Yabuke; Real, Luiz Gustavo dos Santos; Oliveira, Nelson Antônio de; Nalesso, Wellington Poi (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação André José Contel Luiz Gustavo dos Santos Real